Analytical quantification method of protein denaturation in spray drying - Suria, Mahmud (2012)
Protein is the most valuable constituent of bovine milk, due to its high nutritional quality,unique physicochemical and functional properties,which were exploited to manufacture diverse range of dairy products.This research is to identify the protein denaturation by heat in lab scale spray dryer. The Lab-Plant SD06AG Laboratory Scale Spray Dryer is used to produce protein powder from a pure whey protein powder.This work is to establish a method for preserving protein content in whey protein during the spray drying which is by employing the microencapsulation technique and also by controlling the spray drying operating parameters.Protein denaturation was reduced by adding of microencapsulation by using Maltodextrin.The moisture content analysis was determined via MS-07 Moisture Content Analyzer.Then,the morphology and particle size distribution of milk powders are determined by using Malvern Mastersizer.The quality of protein that undergo spray drying process which is before and after it analyzed by using high-performance liquid chromatography (HPLC).The analysis suggested a severe protein denaturation (60% and 40%) at higher spray drying temperature (180 °C and 190°C) but can be reduced up to 29% and 20% when microencapsulation technique is employed.